Serum melatonin levels in patients with traumatic brain injury-induced coma - Qiu, Wusi; Jiang, Qizhou; Xiao, Guoming (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2015)
Introduction : Melatonin (MLT) is a known antioxidant. We present here the changes of serum melatonin levels in adult patients with traumatic brain injury (TBI)-induced coma. Material and methods : Sixty-one adult patients with TBI-induced coma, assessed according to Glasgow Coma Scale (GCS) scores on admission, were divided into very severe injury, severe injury and moderate injury groups. Thirty-one adult healthy volunteers were selected as the control group. Blood samples were collected twice at day 1, day 3 and day 7 after admission. The prognosis of these patients was evaluated 3 months after TBI. Results : The serum MLT levels of each TBI group at each time point were significantly lower than those of the control group (p < 0.05). The MLT levels of very severe and severe TBI groups were significantly lower than those of the moderate TBI group (p < 0.05). The MLT level of the very severe group was significantly lower than that of the severe group (p < 0.05). The lower the serum MLT level, the more severe was the condition of TBI (by GCS scoring), and the lower were the Glasgow Outcome Scale (GOS) scores. Conclusions : Lower serum MLT levels may indicate worse condition, and serum melatonin levels may correlate with the severity and prognosis of patients with TBI.